Research on Capability Optimization of High Maneuvering Combat Force Based on Mission Completion Quality. (June 2020) - Liu, Qian; Lu, Yunjun; Zhang, Bin; Jin, Yiqiao
Abstract: In order to optimize the capability of high maneuvering combat force, considering the non-measurability of capability, a capability optimization method based on mission completion quality is proposed in this paper. In this method, the capability optimization objective is replaced by the mission completion quality, and the quality is measured by the mission completion success rate and the mission completion cost. The optimal solution set which is the path with highest success rate and lowest cost is obtained based on the improved NSGA-II. In light of the cost value of each path in this solution set, the solution has various optimization directions. Based on the actual requirements of mission, decision maker can select one from optimal solution set. Thus, the capability of high maneuvering combat force is optimized.